Training Needs of Poultry Farmers in Hilly Areas - Sahu, R. P.; Singh, N. K. (Indian Journal of Extension Education, 2014)
Temperature of brooder, time of removal of chick guard, type of brooding system, method of providing feed to the  brooding chicks, duration of heating brooder, house before chicks to brood, number of brooding days and purpose of chick  guard, were perceived by the poultry farmers as more important training needs in brooding practices. While the aspects  like percentage of moisture to be maintained in litter, period of regular and slight hoeing of litter in a viable shed, thickness  of litter material to be added every month, replacement of litter from a viable poultry unit and basic qualities of the litter  material were considered as more important training needs under litter management practices. The poultry farmers  perceived that dose of fowl pox vaccine, age at which vaccination against fowl pox is done, dose of mareek's disease  vaccine, age at which vaccination against mareek's disease is done, medicine used to kill internal parasites and rate of  coccidistat for mixing with feed were the more important training needs in vaccination practices. Whereas, under feeding  practices, source of vitamin in feed, source of protein in feed, source of minerals in feed and source of carbohydrates in  feed were considered as more important training needs. Training assumes a special recognition in view of growing  sophistication in poultry farming and allied technology. In order to make a training more meaningful and effective, the  training needs of the poultry farmers have to be identified before implementing any training programme. The present  study was undertaken with the objective to assess the training needs of poultry farmers in Bageshwar district of  Uttarakhand.
Keywords: Training needs; litter management practices; vaccination practices